Angiolymphoid Hyperplasia with Eosinophilia- Think Twice with Scalp Papules! A Case Report - Pooja Agarwal; Kalgi Baxi; Malhar Shah (Nepal Journal of Dermatology, Venereology & Leprology)
Angiolymphoid hyperplasia is an uncommon condition characterized by multiple erythematous papules and nodules which are vascular and present over the head and neck area, predominantly around the ears. It is a benign condition but treatment is often sought for the appearance of lesions. We report a case that had a recurrence of erythematous lesions after incomplete electrocoagulation and the diagnosis of angiolymphoid hyperplasia with eosinophilia was confirmed on histopathological evaluation after complete excision of the lesion. In conclusion, as angiolymphoid hyperplasia can be clinically misdiagnosed, histopathological evaluation is warranted in erythematous nodules presenting over the sites of predilection.